Workshop Penulisan Artikel Ilmiah dan Publikasi di Fakultas Bahasa dan Seni (FBS) Unsiq Wonosobo - Sukarni, Semi; Sudar, Sudar; Rokhayati, Titi (Abdibaraya, 2024)
The objectives of the community service that will be carried out by the English Language Education Study Program service team include: (1) Providing an explanation regarding the form of the final assignment as a substitute for the student's thesis; (2) Provide an explanation of how to compose a scientific article as a substitute for a student's thesis; (3) Provide an explanation of how to publish scientific articles as a substitute for student theses. The service partners are students and lecturers of English Language Education and English Literature, Faculty of Languages and Arts, UNSIQ, Wonosobo. The community service was carried out on May 29 2024 in Room A5 FBS UNSIQ, which was attended by 41 participants. The results of this activity can be described one by one as follows: (1) Participants are able to understand the policy regarding writing final assignments as one of the requirements for undergraduate graduation; (2) Participants are able to understand the technicalities of writing scientific papers which include the elements which include Abstract, Introduction, Methods, Results and Discussion (AIMRAD; (3) participants are able to understand the technical prerequisites for publishing scientific articles in journals and the stages. Bearing in mind the target of graduates must be able to publish articles in accredited national journals, especially Sinta 2. For those who will replace their final thesis assignment, students are expected to read as many references to accredited scientific journal articles as possible on topics they are interested in so that students are able to find research gaps as a guide in their research as material for write scientific articles